The Putumayo Indians and the Rubber Boom (2011)
This article approaches the Putumayo Indians’ memory of the Rubber Boom, in the voice of the Muinane group coming to grips with their painful memories of that violent past, and in the recent initiative of the Colombian government to declare the reconstructed headquarters of the Peruvian Amazon Company in La Chorrera as a ‘Estate of Cultural Interest’. This memory is represented by Indians in the double image of the Basket of Darkness, which holds the memories of violence, and the Basket of Life, which holds the seeds of the future looking forward to the growing of new generations and leaving behind the dangerous memories of violence and sorcery of the past.